Impact of nicotine product use on outcomes of patients receiving cervical disc arthroplasty: a propensity score analysis of the united States nationwide inpatient sample 2005–2020 - Lin, Yu-Jun; Shih, Fu-Yuan; Huang, Jin-Fu; Ting, Chun-Wei; Tsai, Yu-Chin; Chang, Lin; Wang, Hung-Cheng; Chen, Wu-Fu (Journal of orthopaedic surgery and research, 2025)
Nicotine product use, including cigarette smoking and other nicotine products, is a known risk factor for various health complications. While previous studies have examined its impact on spinal procedures, its specific effects on cervical disc arthroplasty (CDA) remain unclear. This study aims to investigate the association between nicotine product use and inpatient outcomes in patients undergoing CDA. Data from the 2005 to 2020 US Nationwide Inpatient Sample database of hospitalized adults ≥ 18 years old who underwent primary or revision CDA were extracted. Patients were divided into nicotine product users and non-users. Propensity score matching (PSM) was employed to balance the baseline characteristics between the groups. In-hospital mortality, unfavorable discharge, length of stay (LOS), and complications were compared between nicotine product users and non-users through logistic regression analyses. After 1:1 PSM, 5,562 patients were included in the analysis. After adjustment, nicotine product users had a significantly elevated risk of overall complications (adjusted odds ratio [aOR] = 1.37, 95% confidence interval [CI]: 1.13-1.66, p = 0.002) and infection (aOR = 1.74, 95% CI: 1.17-2.58, p = 0.006). No significant association was observed between nicotine product use and the risk of unfavorable discharge or prolonged LOS (both, p > 0.05). In stratified analyses, male, but not female nicotine product users, had a greater risk of infection (aOR = 2.12, 95% CI: 1.22-3.70, p = 0.008). Nicotine product use was significantly associated with higher infection risk among individuals without diabetes, obesity, and chronic pulmonary disease (p < 0.05). Nicotine product use is associated with a higher risk of complications following CDA, particularly infections. The study highlights the importance of considering nicotine product use during preoperative assessments and postoperative care for patients undergoing CDA.